Kepayang (Pangium edule Reinw), PENGARUH PEMBERIAN EKSTRAK PROTEIN TOTAL KOTILEDON BIJI KEPAYANG (Pangium edule Reinw) TERHADAP PENGGUMPALAN SPERMATOZOA SAPI ( Bos taurus ) - Sitorus, Lizken; Haryanto, Hery; Ruyani, Aceng (UNIB Press, 2025)
The effect of administering total cotyledon protein extract from kepayang seeds (Pangium edule Reinw) on cow spermatozoa (Bos taurus) was conducted from March - April 2015, in the Basic Science laboratory of biology, FMIPA UNIB and the biology garden of FKIP UNIB. The purpose of this study was to explain the effect of administering total cotyledon protein extract from kepayang seeds on the agglomeration of cow spermatozoa. The steps of this study were the total cotyledon protein of kepayang seeds extracted, protein precipitation, determination of total cotyledon protein content of kepayang seeds (P. edule), and treatment of cow spermatozoa agglomeration. The analysis used was ANOVA with 10 treatments and 3 repetitions. Based on the results of data analysis, the sediment at 50% ammonium sulfate gave an average coagulation time of bovine spermatozoa of 132 seconds with a total protein content of 56.15 mg/mL.